RECOGNITION OF INCOME AND EXPENDITURE AND THEIR REFLECTION IN THE FINANCIAL STATEMENTS (Euro-Asia Conferences, 2021)
Currently, income accounting in state (municipal) institutions is carried out in accordance with the accounting instructions (depending on the type of institution). These documents provide accounts for the accounting of income and correspondence of accounts to reflect transactions related to them, as well as the general procedure for the measurement and recognition of income.